Pengaruh Hasil Belajar Psikologi Islam Terhadap Etika Sosial Mahasiswa PAI FIS UNJ - Ahmad Reza Maulana; Arlino Pratama; Akhmad Nawawi Al Khoyri; Iftinani Lulu Nabila; Tajriyah Tajriyah (Universitas Maritim AMNI Semarang, 2024)
This research aims to analyze the influence of Islamic psychology learning outcomes on the social ethics of students in the Islamic Religious Education (PAI) study program at the Faculty of Science, University of Jakarta (fis-fis ungmu. The research method used is quantitative using regression design. This research sample consists of 30 Pai Fis UNJ Students Selected Randomly. Data was collected through a questionnaire that measured students' Islamic psychology and social ethics learning outcomes. The results of data analysis showed that there was no significant influence between Islamic psychology learning outcomes and students' social ethics that there are other factors that can influence social ethics.